PERANCANGAN SIGN SYSTEM PADA MASTER PLAN KAMPUS UNIVERSITAS NEGERI PADANG - MUHAMMAD HABIB HENDRIZAL, Ir. Drs. Heldi, M.Si., Ph.D., Hendra Ariwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The development of Padang State University towards quality universities is supported by the improvement of facilities, infrastructure, building facilities, transportation and management. However, the existing sign system facility has not been optimally integrated for the benefit of facilities for campus communities such as: Direction sign, identification sign, and information sign. The purpose of designing a sign system in the master plan of Padang State University as an informative, communicative and effective direction.The design method used is descriptive qualitative with an analysis approach of 5W + 1H (what, where, when, who, why, how), to see the issues raised. The main media used: Identification sign, direction sign, and information sign, besides supporting media for manual book, calendar, note book, work agenda book, and flayer.Keyword: Sign System, Padang State University, Media